2012
DOI: 10.1364/oe.20.005319
|View full text |Cite
|
Sign up to set email alerts
|

TEM_00 mode content of a two stage single-frequency Yb-doped PCF MOPA with 246 W of output power

Abstract: Gravitational wave detectors require linearly polarized single-frequency laser sources with a high fractional TEM 00 mode content. We investigated the modal decomposition of a polarization maintaining photonic crystal fiber with a mode field diameter of 29 µm, operating in a single-frequency master-oscillator power-amplifier scheme, with respect to the TEM nm modes. Low degradation of the beam quality with increasing pump power could be observed, while a maximum power in the TEM 00 mode of 203 W was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…shows that the beam contains above 94% in the fundamental Gaussian mode, which is similar to other results that have been reported with this type of fiber [12]. (ii) The beam jitter is critical for a wide range of applications especially in GW detection.…”
Section: W Fiber Amplifier Output Characterizationsupporting
confidence: 89%
“…shows that the beam contains above 94% in the fundamental Gaussian mode, which is similar to other results that have been reported with this type of fiber [12]. (ii) The beam jitter is critical for a wide range of applications especially in GW detection.…”
Section: W Fiber Amplifier Output Characterizationsupporting
confidence: 89%
“…2, right), which has been confirmed by the analysis with and transmission through a non-confocal ring cavity and is, to the best of our knowledge, the highest TEM 00 power measured [3]. Using large core fibers (e.g.…”
Section: Amplifier Setup and Power Scalingsupporting
confidence: 69%
“…In recent years, several (monolithic) single-frequency fiber amplifiers have been developed that demonstrated the power scalability of such devices. In 2012, Karow et al [9] reported a free-space pumped photonic crystal fiber based amplifier with 203 W of output power in the TEM 00 -mode. Additionally, no noise increase in the MHz range was observed with the conclusion of a truly SBS-free amplifier.…”
Section: Introductionmentioning
confidence: 99%